2019
DOI: 10.3390/ijms20215412
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Transcriptome, Selected Intracellular Signaling Pathways, Proliferation and Apoptosis of LNCaP Cells Exposed to High Leptin Concentrations

Abstract: Leptin, the first discovered adipokine, has been connected to various physiological and pathophysiological processes, including cancerogenesis. Increasing evidence confirms its influence on prostate cancer cells. However, studies on the effects of leptin on the proliferation and apoptosis of the androgen-sensitive LNCaP line of prostate cancer cells brought conflicting results. Therefore, we performed studies on the effects of high LEP concentration (1 × 10−6 M) on gene expression profile, change of selected s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 85 publications
1
13
0
Order By: Relevance
“…First of all, 512 robust DEGs between breast tumor tissues and normal breast tissues were identi ed using RRA method. Among them, COL11A1, S100P, LEP and FGF2 are the most signi cant DEGs, which have been reported to be associated with the pathogenesis and development of breast cancer [38][39][40][41]. Functional annotation analysis revealed that the robust DEGs signi cantly enriched in many GO terms associated with proliferation and energy metabolism, such as extracellular matrix organization, extracellular structure organization, mitotic nuclear division, regulation of lipid metabolic process, and glycosaminoglycan binding, which were consistent with published data [42][43][44].…”
Section: Discussionsupporting
confidence: 88%
“…First of all, 512 robust DEGs between breast tumor tissues and normal breast tissues were identi ed using RRA method. Among them, COL11A1, S100P, LEP and FGF2 are the most signi cant DEGs, which have been reported to be associated with the pathogenesis and development of breast cancer [38][39][40][41]. Functional annotation analysis revealed that the robust DEGs signi cantly enriched in many GO terms associated with proliferation and energy metabolism, such as extracellular matrix organization, extracellular structure organization, mitotic nuclear division, regulation of lipid metabolic process, and glycosaminoglycan binding, which were consistent with published data [42][43][44].…”
Section: Discussionsupporting
confidence: 88%
“…38 A study of LNCaP cells showed that apoptosis and proliferation inhibition induced by exposure to high concentrations of leptin were associated with reduced p38 MAPK expression. 39 Nontoxic EEAC can reduce the expression of GLUD1 in hepatoma cells, and it can inhibit the migration of hepatoma cells by the down-regulation of MAPK. 40 These studies remind us that p38 may be a link in which GLUD1 changes the behavior of prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The microarray study was performed as described in detail elsewhere ( 15 18 ). The total RNA isolated previously was pooled into four samples per group (control, ACTH, forskolin and adropin) treated as described above (see Cell culture and Treatment section).…”
Section: Methodsmentioning
confidence: 99%